HUKUM KEWARISAN ISLAM BERDASARKAN SEJARAH, HUKUM, ASAS-ASAS KEWARISAN - M. Iqbal; Nurul Latifah Hamzah (Jurnal Syariah dan Ekonomi Islam, 2024)
This study explains the concept of inheritance in Islam, a system that regulates how a deceased treasure is given to his heirs. Inheritance, also known as a faraid, is a certain portion of the treasure given to the heir and is a way to show devotion to the Creator. The inheritance of Islam is closely related to the faith, which is reflected in the practice of the Quran and the Sunnah of His Messenger. The main principle is the principle of equity for men and women, in which both rights are considered equal, although the sum of rights may differ, as long as the respective rights and obligations are equal and equitable. For a successful inheritance division, every heir must understand the law of inheriting. From Arab tradition to Islamic influence, this study deals with the history of heritage in Islam. In addition, he revealed a lack of understanding of the Muslim community about heritage today.The research methodology is qualitative and uses library sources to gather data. Important factors such as the definition of inheritance, its legal basis, and the principles of Islamic heritage are discussed in depth. The aim of this study is to improve the understanding of the Muslim community and to ensure the implementation of the teachings of Islam by further explaining the history, laws, and procedures for implementing the division of inheritance in Islam. This research has resulted in a broader understanding of Islamic heritage not only as a rule of sharing wealth but also as value.